Evolución reciente y claves actuales del Derecho Urbanístico Español - Iglesias González, Felipe (2022)
The purpose of this paper is to analyse the evolution of Spanish urban law in democracy. Spanish urban regulation has gone from a homogeneous state regulation to an increasingly heterogeneous regional regulation. For these purposes, the ruling of the Constitutional Court 61/1997, of March 20, was key, which encouraged the autonomous communities to approve their own urban codes, initiating a process of regulatory diaspora that continues. The most representative content of current state legislation is also studied, from the basic situations of land to the regime of transformation actions, through the valuation regime.